A systematic review of the childbearing needs of single-child couples - Fatemeh Seraj Shirvan; Maryam Moradi; Robab Latifnejad Ruodsari (BMC, 2024)
Abstract Background Nowadays, the challenge of having single child is spreading in many countries. Only- child family is prevalent in 26% of families in Canada, 21% in the United States, 47.5% in Europe and 20% in Iran, which can lead to fertility below replacement level. Therefore, the current review was conducted to identify the needs of single-child couples. Methods The PRISMA checklist was used to prepare this systematic review report. English and Persian articles published between 2000 and April 2023 were searched in the English databases of ISI, PubMed, Cochrane library and Google Scholar search engine as well as Persian databases of SID and Magiran using keywords of only child, needs assessment and Reproductive behavior. All cross-sectional and correlational studies that addressed the needs of single-child couples were included in the study. The quality assessment of the articles was done by the STROBE checklist. Data extraction was done by two independent researchers using a self-structured checklist. To analyze the data, following tabulating the extracted data, the process of qualitative synthesis was done for systematic review taking into account ethical considerations. Results Out of 1,581 articles found, 17 articles were included in the systematic review. The needs of single-child couples were divided into four general areas included 1) Financial needs, 2) Cultural needs, 3) Educational needs, and 4) Supportive needs. The support needs included two kinds of social and family support. Conclusion Solving financial needs, creating a culture of positive values of childbearing and men's participation in household affairs, considering women's preferences in order to increase education and employment, childbearing training and counseling and creating social and family support in line with work and family harmony and quality care of children, as the most important needs of single-child couples, should be incorporated in the formulation of childbearing incentive programs.